Climate Change: An Emerging Threat To Nigeria’s National Security - Nwauba, Tochukwu (International Journal of Scientific Research and Management (IJSRM), 2018)
Current and past realities in Nigeria's national security resonates a dominance as well as a reoccurrence of newly emerging and non-conventional security challenges as threats to public safety and stability in the country, despite a seeming propensity to concentrate on traditional and military threats. The attention garnered is enormous within and outside Nigeria following the constant danger to lives and order and other varying forms of social disruptions including heavy casualties. This research delves into a salient aspect of these new and emerging threats: Climate change. It finds that climate change is the most formidable threat security in Nigeria in recent time and going into the future; human and state alike. In addition to having a broader impact radius; including a high vulnerability as well as low adaptiveness among citizens being a developing country, the effects of climate change on the Nigerian society could be more destructive than analysts’ project meaning current impacts may yet be minimal. Hence drawing a critical need for immediate response and action. The paper submits that the attempt to contain this rising threat must incorporate higher securitization of the threat and its various forms; investment into public sensitization on the phenomenon; a general capacity building on alertness and crisis response system as well as general adaptivity to harsh outcomes of climate change. This piece equally enjoins a general shift in attitude together with the total reform of the Nigerian security structure to comprise and target threats to human security especially.